Responsibility of Parking Managers for Loss of Helmets of Parking Service Users - Juanda, Juanda; Fauzi, Chairul (RESAM Jurnal Hukum, 2024)
The parking manager has the obligation to maintain the vehicle and return it in the same condition when the vehicle was deposited as stipulated in Article 1706 and Article 1714 of the Civil Code. However, in practice parking managers are not responsible for the loss of goods in the form of helmets belonging to parking service users as happened in the parking area of Pasar Paya Ilang. The purpose of this study isto find out the responsibility of parking managers for losing helmets of parking service users. This type of empirical juridical research or called field research examines applicable legal provisions and what happens in reality in society. The nature of this study is descriptive analytical. The results of this study explain the responsibility of parking managers for the loss of helmets of parking service users, parking officers or parking managers in the parking area of Pasar Paya Ilang are not responsible for the loss of belongings belonging to consumers or users of parking services, parking managers are only responsible for helping to find lost items in the parking area of Pasar Paya Ilang only, this is contrary to Article 1694 of the Civil Code,   and also contrary to  Article 7 letter f and Article 19 paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection.